Clonal Emergence of Invasive Multidrug-Resistant Staphylococcus epidermidis Deconvoluted via a Combination of Whole-Genome Sequencing and Microbiome Analyses. (12th March 2018) - Li, Xiqi; Arias, Cesar A; Aitken, Samuel L; Galloway Peña, Jessica; Panesso, Diana; Chang, Michael; Diaz, Lorena; Rios, Rafael; Numan, Yazan; Ghaoui, Sammi; DebRoy, Sruti; Bhatti, Micah M; et al.
Abstract : A marked increased in linezolid resistance among invasive Staphylococcus epidermidis was due to dissemination of a cfr -containing clone of S. epidermidis that dominated the gastrointestinal microbiota of patients following receipt of linezolid. Abstract: Background: Pathobionts, bacteria that are typically human commensals but can cause disease, contribute significantly to antimicrobial resistance. Staphylococcus epidermidis is a prototypical pathobiont as it is a ubiquitous human commensal but also a leading cause of healthcare-associated bacteremia. We sought to determine the etiology of a recent increase in invasive S. epidermidis isolates resistant to linezolid. Methods: Whole-genome sequencing (WGS) was performed on 176 S. epidermidis bloodstream isolates collected at the MD Anderson Cancer Center in Houston, Texas, between 2013 and 2016. Molecular relationships were assessed via complementary phylogenomic approaches. Abundance of the linezolid resistance determinant cfr was determined in stool samples via reverse-transcription quantitative polymerase chain reaction. Results: Thirty-nine of the 176 strains were linezolid resistant (22%). Thirty-one of the 39 linezolid-resistant S. epidermidis infections were caused by a particular clone resistant to multiple antimicrobials that spread among leukemia patients and carried cfr on a 49-kb plasmid (herein called pMB151a). The 6 kb of pMB151a surrounding the cfr gene was nearly 100% identical to a cfr -containing plasmid isolated from livestock-associated staphylococci in China. Analysis of serial stool samples from leukemia patients revealed progressive staphylococcal domination of the intestinal microflora and an increase in cfr abundance following linezolid use. Conclusions: The combination of linezolid use plus transmission of a multidrug-resistant clone drove expansion of invasive, linezolid-resistant S. epidermidis . Our results lend support to the notion that a combination of antibiotic stewardship plus infection control measures may help to control the spread of a multidrug-resistant pathobiont.